2021
DOI: 10.3390/antiox10050747
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Phenethyl Ester Protects Kidney Mitochondria against Ischemia/Reperfusion Induced Injury in an In Vivo Rat Model

Abstract: To improve ischemia/reperfusion tolerance, a lot of attention has been focused on natural antioxidants. Caffeic acid phenethyl ester (CAPE), an active component of the resinous exudates of the buds and young leaves of Populus nigra L., Baccharis sarothroides A., etc., and of propolis, possesses unique biological activities such as anti-inflammatory, antioxidant, immunomodulating, and cardioprotective effects, among others. There is a lack of studies showing a link between the antioxidant potential of CAPE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Moreover, our in vitro results using the FRAP method revealed that both fractions from both Artemisia species' herb acetone extracts possess reducing properties. Therefore, we assume that Artemisia species fractions rich in caffeoylquinic acids can be suitable candidates for the modulation of mitochondrial function and regulation of mitochondrial redox state in the cells by suppressing ROS production and reducing cytochrome c. This finding is in agreement with our previous study showing that the ester of caffeic acid (caffeic acid phenethyl ester), which has a similar chemical structure to caffeoylquinic acids, also effectively reduces cytochrome c [28]. Our results are supported by the results of other scientists who have also investigated the role of cytochrome c redox state in the occurrence of apoptosis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, our in vitro results using the FRAP method revealed that both fractions from both Artemisia species' herb acetone extracts possess reducing properties. Therefore, we assume that Artemisia species fractions rich in caffeoylquinic acids can be suitable candidates for the modulation of mitochondrial function and regulation of mitochondrial redox state in the cells by suppressing ROS production and reducing cytochrome c. This finding is in agreement with our previous study showing that the ester of caffeic acid (caffeic acid phenethyl ester), which has a similar chemical structure to caffeoylquinic acids, also effectively reduces cytochrome c [28]. Our results are supported by the results of other scientists who have also investigated the role of cytochrome c redox state in the occurrence of apoptosis.…”
Section: Discussionsupporting
confidence: 92%
“…For antioxidant activity evaluation, all tested fractions and acetone extracts were dissolved in 70% ethanol until complete dissolution, obtaining a concentration of 0.5 mg/mL. Spectrophotometric assays were implemented as described by Raudone et al [ 27 ] and in our previous report [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations